Characteristic study of flat spray nozzle by using Particle Image Velocimetry (PIV) and ANSYS simulation method - Pairan, M. Rasidi; Asmuin, Norzelawati; Mat Isa, Nurasikin; Sies, Farid (2022)
Water mist sprays are used in wide range of application. However it is depend to the spray characteristic to suit the particular application. This project studies the water droplet velocity and penetration angle generated by new development mist spray with a flat spray pattern. This research conducted into two part which are experimental and simulation section. The experimental was conducted by using particle image velocimetry (PIV) method, ANSYS software was used as tools for simulation section meanwhile image J software was used to measure the penetration angle. Three different of combination pressure of air and water were tested which are 1 bar (case A), 2 bar (case B) and 3 bar (case C). The flat spray generated by the new development nozzle was examined at 9cm vertical line from 8cm of the nozzle orifice. The result provided in the detailed analysis shows that the trend of graph velocity versus distance gives the good agreement within simulation and experiment for all the pressure combination. As the water and air pressure increased from 1 bar to 2 bar, the velocity and angle penetration also increased, however for case 3 which run under 3 bar condition, the water droplet velocity generated increased but the angle penetration is decreased. All the data then validated by calculate the error between experiment and simulation. By comparing the simulation data to the experiment data for all the cases, the standard deviation for this case A, case B and case C relatively small which are 5.444, 0.8242 and 6.4023.